Análisis de las relaciones diplomáticas entre la Unión Europea y Ecuador luego de la firma del Tratado Multipartes - Almeida Ortiz, Carla (2024)
This research aims to analyze whether the Multiparty Agreement between Ecuador and the European Union, which came into effect in 2017, has influenced the diplomatic relations between the two parties. The study is grounded in the theories of liberalism and neoliberalism within the field of international relations, which emphasize the importance of economic cooperation and interdependence as key factors for the development of stable and peaceful relations between states. Based on these theories, the research explores the possibility that a trade agreement, beyond its economic benefits, may affect the diplomatic dynamics between the signatory parties. The methodology used in this research is qualitative and based on a longitudinal design, allowing for the observation and analysis of changes in the diplomatic relations between Ecuador and the European Union over time, particularly during the period 2017-2022. Data collection methods include semi-structured interviews with key actors involved in the implementation and evaluation of the Multiparty Agreement, as well as the review of relevant primary and secondary sources. Data triangulation was employed to ensure the validity and reliability of the findings, combining information from different sources and perspectives. Among the main findings of the research is that, while the Multiparty Agreement has led to a significant increase in bilateral trade, with economic benefits for both parties, its impact on diplomatic relations has not been as thoroughly detailed. On one hand, the agreement has strengthened cooperation in key areas such as sustainable development, technology, and innovation, and has created new opportunities for bilateral collaboration. However, it has also generated challenges, particularly concerning the compliance with European regulations and standards. The study concludes that the Multiparty Agreement has had a positive effect on the bilateral relationship but has introduced complexities that require careful diplomatic management to maximize its benefits and mitigate potential frictions.